2015
DOI: 10.1080/10615806.2015.1058369
|View full text |Cite
|
Sign up to set email alerts
|

Associations between job burnout and self-efficacy: a meta-analysis

Abstract: Significant self-efficacy-burnout relationships were observed across countries, although the strength of associations varied across burnout components, participants' profession, and their age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
257
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(294 citation statements)
references
References 93 publications
23
257
1
13
Order By: Relevance
“…Additionally, we aimed to investigate the effect of exercise on five secondary outcomes of employee well-being: self-efficacy, sleep, work ability, cognitive functioning, and aerobic fitness. Prior work shows that fatigued employees often show deficiencies in these outcomes (20)(21)(22)(23)(24), while it has been suggested that exercise positively affects them (25)(26)(27)(28)(29), see 30 for a more extensive justification for the choice of secondary outcomes). We therefore expected that exercise improves general and work-related self-efficacy, sleep quality and quantity, work ability, cognitive functioning, and aerobic fitness.…”
mentioning
confidence: 99%
“…Additionally, we aimed to investigate the effect of exercise on five secondary outcomes of employee well-being: self-efficacy, sleep, work ability, cognitive functioning, and aerobic fitness. Prior work shows that fatigued employees often show deficiencies in these outcomes (20)(21)(22)(23)(24), while it has been suggested that exercise positively affects them (25)(26)(27)(28)(29), see 30 for a more extensive justification for the choice of secondary outcomes). We therefore expected that exercise improves general and work-related self-efficacy, sleep quality and quantity, work ability, cognitive functioning, and aerobic fitness.…”
mentioning
confidence: 99%
“…Além dos fatores de stress organizacionais, as variáveis individuais e de autorregulação, como estratégias de coping, locus de controle e a autoeficácia têm desempenhado um importante papel mediador entre os estressores ocupacionais e a Síndrome de Burnout (Alarcon, Eschelman, & Bowling, 2009;Shoji et al, 2014). Alguns estudos apontam no sentido de que a que a autoeficácia é um importante recurso pessoal de proteção face a situações de stress e burnout (Brown, 2012;Petitta & Vecchione, 2011), desempenhando um papel fundamental em intervenções, devido a sua possibilidade de modificação.…”
Section: Introductionunclassified
“…A literatura tem evidenciado uma relação negativa entre a autoeficácia e Síndrome de Burnout (Aftab, Shah, & Mehmood, 2012;Fernet, Austin, Trépanier, & Dussault, 2013;Nota, Ferrari, & Soresi, 2007;Shoji et al, 2014;Vegchel, Jonge, Söderfeldt, Dormann, & Schaufeli, 2004;Yang, 2011). No entanto, ainda são escassos estudos que têm procurado identificar o seu papel mediador entre fatores de risco e o Burnout (Carlotto, Dias, Batista, & Diehl, 2015;Prati, Pietrantoni, & Cicognani, 2010;Salanova, Peiró, & Schaufeli, 2002).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Rigelman & Ruben (2012) regarded performance as the impression of the work outcome and attitudes of an individual, a unit, or an organization. Professional performance was "professional affairs done by professional people", which was defined by Shoji et al (2016) in the research on the professional capability and professional performance of human resource developers. Delvauxa et al (2013) proposed that a person with more professional performance could become an "expert"; on the contrary, one without professional characteristics was regarded as a "novice".…”
Section: Environmental Educationmentioning
confidence: 99%